Answer:
Y = (x + 3)(x - 4)(x + 1)^2
Y = (x^2 - x - 12)(x^2 + 2x + 1)
Y = x^4 + 2x^3 + x^2 - x^3 - 2x^2 - x - 12x^2 - 24x - 12
Y = x^4 + x^3 - 13x^2 - 25x - 12
Answer:
The answer is 61.
Step-by-step explanation:
Let, the numbers are: x, (x+2), (x+4)
Now, x+x+2+x+4 = 183
3x + 6 = 183
3x = 177
x = 59
So, second number would be: (x+2) = (59+2) = 61
First let’s establish a few things, The first car can travel 300 miles with 20 gallons of gas, if 14 gallons of gas costs 49.49 then for ever gallon of gas Sam is paying 3 dollars and 53.5 cents. That means for 20 gallons, Sam will need around 71$ for the entire trip if he uses the first car.
Answer:
Step-by-step explanation:
First one is 200 dollars for insurance which will be the constant and 15 dollars an hour which means the equation will be;
C = 15h +200 (Sinking Rivers)
Second one is $30 an hour and $110 for insurance which is the constant so he equation is;
C = 30h + 110 (Floating Down The Stream)
Answer:
the ANWER IS B
Step-by-step explanation:
It B BECAUSE I AM SMART